Resistor Model of Layered Film Structures - Tung Pham Van; E. B. Chubenko; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
Electric properties of film structures consisting of two-dimensional layers, composed by nanocrystalline grains of a semiconductor are proposed to be modeled with an equivalent scheme, in which resistors indicate electrical resistance of current channels in metallic contacts, grain material, potential barriers between grains and layers. Numerical simulation within the model has shown that there is a nonuniform current distribution over the area of the contacts. Current density at their edges can be 3–6 times higher than in the center. Local currents and their distribution in the film bulk are determined by the grain structure of the film, number of the layers, electronic properties of the barriers between grains and layers.